2022
DOI: 10.1093/bjsopen/zrac065
|View full text |Cite
|
Sign up to set email alerts
|

The clinical effectiveness of wound edge protectors in reducing surgical site infection after abdominal surgery: meta-analysis

Abstract: Background Surgical site infection (SSI) is a common complication after abdominal surgery. The effectiveness of wound edge protectors in reducing infection of the surgical sites is still unclear. The purpose of this study was to determine the clinical effectiveness of a wound edge protector (WEP) in reducing SSI rates after abdominal surgery. Methods PubMed, Embase, Web of Science, and the Cochrane Library were systematically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…This was suggested also in a previous similar meta‐analyses study which showed similar promising outcomes for wound protectors in improving the surgical site wound infection and reducing the dual‐ring wound protectors. 6 , 7 , 8 Well‐conducted randomised controlled trials are needed to assess these factors and the combination of different gender, ages, ethnicity and other variants of subjects; because our meta‐analysis study could not answer whether different gender, ages and ethnicity are related to the results.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This was suggested also in a previous similar meta‐analyses study which showed similar promising outcomes for wound protectors in improving the surgical site wound infection and reducing the dual‐ring wound protectors. 6 , 7 , 8 Well‐conducted randomised controlled trials are needed to assess these factors and the combination of different gender, ages, ethnicity and other variants of subjects; because our meta‐analysis study could not answer whether different gender, ages and ethnicity are related to the results.…”
Section: Discussionmentioning
confidence: 99%
“…The expense of these kinds of gadgets is a deterrent to their widespread use 5 . The efficiency of wound protectors in reducing surgical site wound infections in abdominal surgeries has been the subject of multiple meta‐analyses published recently 6‐8 . In lower gastrointestinal surgery, there is not a published meta‐analysis that focuses solely on wound protectors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, analyses of OA have compared their effectiveness against intravenous antibiotics alone, 11 or studied them in combination with mechanical bowel preparation and compared them to MBP 11 or no MBP, respectively. 12 Many early trials were also of poor quality and recruited heterogeneous patient cohorts with both benign and malignant disease undergoing both open and minimally invasive surgical procedures ( Table 1 ).…”
Section: Mechanical Bowel Preparation With Oral Antibioticsmentioning
confidence: 99%
“…Among 41 randomized patients, those using the retractor experienced a significant reduction in SSIs compared with the nonretractor group, with statistical analysis supporting its effectiveness (odds ratio, 8.5; P = .03). A 2022 meta-analysis by Li et al, 5 including 22 randomized clinical trials with 4492 patients, showed wound-edge protector dev ices effectively decreased SSI in clean-contaminated and contaminated surgical procedures.…”
mentioning
confidence: 99%